2016
DOI: 10.5232/ricyde2016.04402
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas de la Escala de Motivación en el Deporte revisada (SMS-II) adaptada al español hablado en México.

Abstract: El objetivo de este estudio fue examinar las propiedades psicométricas (estructura factorial, fiabilidad, validez de constructo) de una versión en español hablado en México de la Escala de Motivación en el Deporte revisada (SMS-II) compuesta por 18 ítems que miden seis factores de regulación conductual planteados por la teoría de la autodeterminación, y probar un modelo que permitiese evaluar la motivación autónoma y la motivación controlada. Participaron 279 deportistas de alto rendimiento con una edad promed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
3
17
0
4
Order By: Relevance
“…In relation to the hypothesis, the results obtained after and analysis of the psychometric properties show adequate validity and reliability levels in the six first-order factors with 18 items, except for AMO and INTEGR, which is line with the results in Viciana et al [53], Pineda-Espejel et al [52], and Beddoes [80], in demotivation and introjected regulation). However, it is worth noting that in Viciana et al [53], for sports, Cronbach’s alpha, Omega, and AVE values for INTEGR (0.686, 0.696, 0.434, respectively) and EXTR (0.536, 0.552, 0.300, respectively) were inadequate.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In relation to the hypothesis, the results obtained after and analysis of the psychometric properties show adequate validity and reliability levels in the six first-order factors with 18 items, except for AMO and INTEGR, which is line with the results in Viciana et al [53], Pineda-Espejel et al [52], and Beddoes [80], in demotivation and introjected regulation). However, it is worth noting that in Viciana et al [53], for sports, Cronbach’s alpha, Omega, and AVE values for INTEGR (0.686, 0.696, 0.434, respectively) and EXTR (0.536, 0.552, 0.300, respectively) were inadequate.…”
Section: Discussionsupporting
confidence: 88%
“…The CFA results were also adequate, both for absolute and incremental fit indices, in line with other studies, such as Pelletier et al [46], Pineda-Espejel et al [52], and Viciana et al [53]. The latter study found similar RMSEA and CFI values, though they improved in their five-factor model with the elimination of some problematic items (RMSEA = 0.044; CFI = 0.966).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Competitive anxiety in sport was measured using the Spanish-language adaptation (Escala de Ansiedad Competitiva, [29] of the Sport Anxiety Scale 2 (SAS-2) [30]. The SAS-2 consists of three 5-item scales to measure three factors: somatic anxiety, worry, and lack of concentration or deconcentration.…”
Section: Instruments and Materialsmentioning
confidence: 99%